AKIBAT HUKUM PERALIHAN PERKAWINAN BIASA MENJADI PERKAWINAN NYENTANA TERHADAP KEDUDKAN HAK WARIS MENURUT HUKUM ADAT BALI - Made Widja Candrasari; Ida Ayu Sadnyini (Universitas Pendidikan Nasional, 2019)
Current developments show that people not only do ordinary marriages, but also marriage. Developing from the transition of ordinary marriage to a nyentana marriage, while the main issues of this study are (1). What factors are the causes of the transition from ordinary marriage to a comfortable marriage? (2). What is the implementation and legitimacy of the transition of ordinary marriages to safe marriage? (3). What is the consequence of the law of the transition of ordinary marriage to a marriage of interest to the position of inheritance rights according to Balinese Customary Law. The theory used is the theory of Eugen Ehrlich which states that the law lives and develops in society and the theory of legal protection from Philpus M.Hadjon. This study uses empirical legal research methods. The results of the study showed that the factors that caused the transition of marriage, the legitimate implementation of the marriage transition, and inheritance in Balinese customary law. The conclusion of this study was that there were no sons as the next generation of family descendants and successors to family inheritance, the implementation of the legal marriage was recorded in the respective Pakraman villages and civil records, to inheritance rights, all material inheritance rights and immaterial property fell to the status of women purusa. The transfer of marriage is obliged to ask for the stipulation of the transition marriage from an ordinary marriage to a marriage, to a local district court.Keywords: Transition of Marriage, Balinese Customary Law.